Internationalization of emerging market firms: the case of Turkish retailers - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2010)
Purpose - The purpose of this paper is to understand the internationalization process (IP) of retailing firms from emerging markets and to determine a new focus and/or modifications if necessary in the established Western-based theories. Design/methodology/approach - The paper follows an exploratory approach utilizing qualitative multiple case studies. Data are collected through eight in-depth interviews with senior managers of four Turkish retail firms in textile and ready-to-wear industry. An inductive approach is followed. Findings - It is found that internal drivers, home and host country characteristics and matching have an impact on the IP of retail firms from emerging markets. A table is formed to compare and contrast IF in the context of developed country, emerging market, and Turkish retail firms. Also a model is proposed to understand the IP of Turkish retail firms. Research limitations/implications - The proposed model of IP for Turkish retail firms provides an initial point for building theory in this quite new area of research. Originality/value - This paper is among the first attempts to study the IF of Turkish retail firms, but it does not intend to claim generalizability to all emerging country firms.
Keywords: Retailing; Emerging markets; Textile industry; International marketing; Globalization; Turkey; DIRECT-INVESTMENT; PERFORMANCE; STRATEGIES; NETWORKS; MULTINATIONALS; DETERMINANTS; ECONOMIES; MOTIVES; MODEL